Transformation of Accounting Education through Game-Based Learning: Implementation of Quizizz at SMK Negeri 1 Surakarta - Martino Ferdinan; Surya Jatmika (Journal of Educational Sciences, 2026)
Accounting learning in Vocational High Schools (SMK) often faces challenges such as low student motivation, monotonous teaching methods, and suboptimal integration of digital media. This study aims to describe the implementation of Quizizz digital learning media in accounting subjects at SMK Negeri 1 Surakarta. The research employed a qualitative approach with a case study design. Subjects consisted of accounting teachers and students from grades X and XI. Data collection techniques included observation, interviews, and documentation, while data analysis used interactive analysis comprising data reduction, data presentation, and conclusion drawing. The findings indicate that Quizizz implementation was carried out systematically through planning, implementation, and evaluation stages. In planning, teachers prepared varied questions aligned with learning objectives. During implementation, students actively engaged through their digital devices, creating an interactive and enjoyable game-based learning atmosphere. In evaluation, Quizizz functioned as a formative assessment tool providing immediate real-time feedback. Student responses were generally positive, as Quizizz enhanced learning motivation, participation, and material comprehension. However, several challenges were encountered, including limited internet connectivity, time management issues, and constraints in presenting practical accounting materials. In conclusion, Quizizz can serve as an effective alternative digital learning medium to improve accounting instruction quality, provided that proper management and adequate facilities are ensured.